कृषाण चन्दरनि गाद्दार (सल’मा) - (:unkn) unknown (Bodo Sahitya Sabha, 2015)
"The book is a Bodo translation of Krisan Chander's novel ""Gaddar"""
Krisan Chander's Gaddar
Keywords: Bodo; literature; Bodo; Bodo